Transcriptional Analysis of the tet(P) Operon from Clostridium perfringens - Johanesen, Priscilla A. (American Society for Microbiology, 2001)
The Clostridium perfringens tetracycline resistance determinant from the 47-kb conjugative R-plasmid pCW3 is unique in that it consists of two overlapping genes, tetA(P) and tetB(P), which mediate resistance by different mechanisms. Detailed transcriptional analysis has shown that the inducible tetA(P) and tetB(P) genes comprise an operon that is transcribed from a single promoter, P3, located 529 bp upstream of the tetA(P) start codon. Deletion of P3 or alteration of the spacing between the −35 and −10 regions significantly reduced the level of transcription in a reporter construct. Induction was shown to be mediated at the level of transcription. Unexpectedly, a factor-independent terminator, T1, was detected downstream of P3 but before the start of the tetA(P) gene. Deletion or mutation of this terminator led to increased read-through transcription in the reporter construct. It is postulated that the T1 terminator is an intrinsic control element of the tet(P) operon and that it acts to prevent the overexpression of the TetA(P) transmembrane protein, even in the presence of tetracycline.